Chad : Poverty Reduction Strategy Paper Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report ;, 2010)
Implementation of Chad's first National Poverty Reduction Strategy was undermined by persistent internal conflict, weak governance, and lack of commitment to and ownership of economic and social reforms. The focus now is on the restoration of security, the improvement of governance, the diversification of the economy, and the promotion of human development. The government has to be mindful of the risks to this strategy. Executive Directors propose that the government should shift away from past patterns and demonstrate commitment to poverty reduction and good governance.